N.I.T (New Ideas Technology): glove marker / Mohd Fakhrunabil Mohd Fareed [et al.] - Mohd Fareed, Mohd Fakhrunabil; Simpol, Luqman Hakim; Libon, Shahijah; Nazri, Siti Sarah Zahidah; Shaari, Nurul Nadhirah (2016)
Our company named New Idea Technology just been established in Malaysia as a company which aims to improve household items to achieve as maximum potential. We have found an innovative way to provide higher efficiency in learning session by introducing "glove marker" to the market.